Inequality : a contemporary approach to race, class, and gender - Keister, Lisa A., 1968-; Southgate, Darby E., 1964- (Cambridge : Cambridge University Press, 2012)
Social stratification is the grouping of people based on income, wealth, political influence and other characteristics. Widely recognized categories such as upper, middle and lower class reflect the presence of social stratification in all societies. Inequality refers to the inevitable disparities in people's positions in this structure. The research presented in this book ranges from studies of income and wealth disparities to analyses of the nature of the class system. This textbook reflects a hybrid approach to studying stratification. It addresses the knowledge accumulated by stratification scholars and challenges students to apply this information to their social world. The authors include a wide range of topics and provide current research to round out their discussions. Each chapter includes a list of key concepts, questions for thought, suggested exercises and multimedia resources.
I: Basic concepts -- Social stratification and opportunities -- Explaining stratification: theories and ideas -- Understanding social stratification: methods of evaluation -- Class and the structure of inequality -- II: Applications -- The upper class and the elite -- The middle class and workers -- The working poor and the underclass -- Social mobility -- Education and inequality -- Women and their changing positions -- Race and ethnicity -- Culture -- Inequality across the globe -- Public policy and social stratification.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: Social stratification -- United States; Equality -- United States; Social classes -- United States; Wealth -- United States; Poverty -- United States